Investigation of flow boiling heat transfer and boiling crisis on a rough surface using infrared thermometry. (October 2020) - Su, G.-Y.; Wang, C.; Zhang, L.; Seong, J.H.; Kommajosyula, R.; Phillips, B.; Bucci, M.
Highlights: We develop a heater to study boiling on rough surfaces using infrared thermometry. A stochastic heat partitioning model captures the boiling curve. The boiling crisis is a critical transition in the near-wall bubble coalescence process. The boiling crisis is captured by a continuum percolation model. Abstract: We design and build a special heater to enable infrared investigations of boiling heat transfer on surfaces featuring the typical roughness and scratch pattern of commercial-grade heat transfer surfaces (in this case a zirconium alloy typically used as fuel cladding material in nuclear reactors). We use high-speed infrared thermometry to investigate surface effects on the boiling process for both the rough infrared heater and a reference more conventional, nano-smooth infrared heater. Compared to the nano-smooth surface, the rough surface has larger nucleation sites, which require a lower nucleation temperature. The rough surface has a much smaller bubble departure volume. However, it has a much higher nucleation site density, and, overall, a higher heat transfer coefficient. We capture this behavior with a stochastic heat flux partitioning model. Notably, while the two surfaces have very different boiling dynamics, the boiling crisis has a common "signature". For both surfaces, the probability density functions of bubble footprint areas follow a power law with a negative exponent smaller than 3, also known as a scale-free distribution. We predict these observations and the onset of the boiling crisis using a continuum percolation model. These results corroborate the hypothesis of the boiling crisis as a percolative critical phase transition of the bubble interaction process.